55. VEPS and OCT in acute and chronic optic neuritis associated with multiple sclerosis. Issue 1 (January 2015) - Di Maggio, G.; Santangelo, R.; Guerrieri, S.; Ferrari, L.; Medaglini, S.; Rodegher, M.; Colombo, B.; Moiola, L.; Del Carro, U.; Martinelli, V.; Comi, G.; Leocani, L.
<x xml:space="preserve">Abstract</x> To evaluate the relative value of optical coherence tomography (OCT) and visual evoked potentials (VEPs) in assessing visual involvement in patients with multiple sclerosis (MS). Cross-sectional study of 121 consecutive subjects with MS. Of 242 eyes, 166 had no previous history of optic neuritis (ON), 22 had a single recent ON episode (<3 months); 54 had chronic ON (at least 1 episode >3 months before). All patients underwent assessment of EDSS, visual acuity (VA), OCT retinal nerve fiber layer (RNFL) thickness and VEP. In eyes with recent ON, the sensitivity of OCT was 5.6% considering only RNFL thickness increase, 38.9% considering also RNFL reduction, with a higher sensitivity of VEP (77.3%; McNemar p < 0.0001 and 0.02). In eyes with chronic ON, no significant difference was found between OCT (68.5%) and VEP (81.5%) sensitivity (VEP/OCT 88.9%). In asymptomatic eyes, VEPs had a higher sensitivity (31.7%) vs OCT (19.9%; p = 0.005); VEP/OCT combined detected abnormalities in 39.2%. In this subgroup, VEP score and global RNFL thickness were significantly correlated with EDSS, disease duration, not with VA. The present findings confirm a higher sensitivity of VEPs in the subacute phases of optic neuritis and in asymptomatic eyes. This discrepancy fades off after more than 3 months from the ON episode. Finally, the correlation with disability and DD favours the usefulness of both techniques in monitoring MS patients, to be verified through longitudinal studies.